A Feasibility Open Trial of a Brief Internet-Delivered Written Exposure Therapy for Worry. Issue 4 (14th January 2019) - Roch-Gagné, Margaux; Talbot, France
Abstract : Background: Cognitive exposure, a treatment of choice for hypothetical fears, involves listening repeatedly to a recorded scenario of one's worst hypothetical fear. A major limitation, however, is that the script cannot be easily modified. Aims: The current study assessed the feasibility of a brief guided internet-based written exposure therapy (iWET) for hypothetical fears, Mind at Peace . Method: Fifty-three adults presenting clinical levels of anxiety (GAD-7 ≥ 8) and worry (PSWQ ≥ 45) were recruited. A single group pre-test/post-test design including a 3-month follow-up was used. Mind at Peace is a 6-week iWET consisting of psychoeducation and five 30-minute weekly writing exposure sessions. Feasibility outcome measures included treatment adherence, attrition, treatment acceptability and preliminary efficacy. Primary outcome measures were the Generalized Anxiety Disorder-7 (GAD-7) and the Penn State Worry Questionnaire (PSWQ). Results: Attrition was higher (57%) and adherence lower (28%) than expected. Intent-to-treat repeated measures ANOVAs revealed significant and large improvements on the GAD-7 (ƞp 2 = 0.36) and the PSWQ (ƞp 2 = 0.23) with similar findings among study completers. Remission rates were higher on the GAD-7 than on the PSWQ, suggesting that Mind at Peace may primarily target general symptoms of generalized anxiety. Rates of acceptability varied, but nearly all study completers reported that they would recommend this treatment to a friend. Conclusions: This study provided valuable information on Mind at Peace . Methodological changes are proposed to improve its feasibility. A more definitive trial incorporating suggested methodological improvements is recommended.